Karakteristik Ekstrak Kulit Buah Kakao (Theobroma cacao L.) sebagai Sumber Antioksidan pada Perlakuan Perbandingan Bahan dengan Pelarut dan Waktu Maserasi - Dwipayanti, Ni Kadek Yeni; Ganda Putra, G.P.; Suhendra, Lutfi (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2020)
Cocoa pod husk is a waste of cocoa processing that is large enough and has not been used optimally. Cocoa pod husk waste can be used more optimally by extracting polyphenols compounds and used as natural antioxidants. This research aims to determine the effect of comparison of materials with solvents and maceration time against cocoa pod husk extracts as a source of antioxidants as well as to determine the material comparison with the solvent and the best maceration time for produce cocoa pod husk extract as a source of antioxidants. The study uses a random design of a group of two factors. The first factor is the comparison of materials with solvents consisting of 1:10, 1:15 and 1:20. The second factor is the maceration time consisting of 24, 36 and 48 hours. The data was analyzed its diversity and continued with the Tukey test. The results of the study showed a comparison of material with solvent and maceration time was very influential to the yield, total phenolic and antioxidant capacity of cocoa pod husk extract. The interaction between treatment is very influential on the total phenolic and antioxidant capacity but has no effect on the cocoa pod husk extract yield. The best treatment to produce cocoa pod husk extract as a source of antioxidant is the comparison of materials with solvent 1:20 and maceration time for 48 hours with a yield characteristic 3.10 ± 0.36 percent, total phenolic at 146 .67 ± 5.14 mg GAE/g and antioxidant capacity 97 .00 ± 2.22 mg GAEAC/g. Keywords: cocoa pod husk extract, comparison of materials with solvents, maceration time, antioxidant.